Situation Analysis and Needs Assessment Report for Rohal Soung Village, Battambang Province, Cambodia - Try, T.; Eam, Dyna; Ferrer, Alice J.; Yen, B.T.; Sebastian, Leocadio S.; Kura Y (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Rohal Suong village is located in Battambang province, Cambodia. The Situation and Needs Assessment was conducted in the village as part of the major initial work to collect data that will serve as baseline information to inform planning of CCAFS intervention and to form the basis for monitoring change over time. The baseline work was conducted in November to December 2014. Rohal Suong is a typical farming village that is moderately diversified, with two rice cropping, some vegetables and fruits, with some surplus to sell in an average year. Rice fields are connected to the Sangke River as a source of water throughout the year and to Tonle Sap Lake and associated flooded forests as a source of fish, firewood, and other animals and plant products. Small-holder agriculture production system prevalent in the village appears to be not very profitable because of the high cost of inputs and limited market and value chain development. Farming families have taken several strategies to increase their overall income by expanding the farming area, intensifying rice production, and seasonal labor migration. These strategies have negative implications: loss of forest and grassland to farmland, degradation of water quality and soil, and labor shortage in the village for agriculture. Raising small livestock is widely practiced as an income generation option, while large livestock is becoming less popular due to the shortage of grazing land. The general perception among the villagers is that the condition of natural resources is declining. Flooded forests are declining because of deforestation and agriculture encroachment. Fisheries resources are declining because of overexploitation and loss of habitats. Meanwhile, the village is also vulnerable to extreme events such flash flood, drought, crop disease and insect outbreak. The village has been supported by a variety of external agents through agricultural development, natural resource management, and food security programs, including some large donor programs, and received in-kind support as well as direct agriculture input subsidies. Several community institutions exist and are functioning well. The local production systems are well adapted to the natural seasonal fluctuation in rainfall and flooding regime, but occasional extreme flooding events cause crop damage and food shortage situation. The existing interventions are not directly associated with specific climate-related issues. There is an opportunity for CCAFS to identify and enhance existing practices that can become good examples of “climate smart agriculture”, and be promoted more widely as such, to increase the general awareness of the importance of climate smart agriculture practices.